The Effect of Flavonoid Consumption on Blood Pressure: A Systematic Review - Wulandari, Citra (Open Access Indonesian Journal of Medical Reviews, 2022)
Hypertension is a common condition in which the long-term force of blood against artery walls is high enough to cause health problems, such as heart disease eventually. High blood pressure is known as the "silent killer". Most people with high blood pressure are unaware of the problem because it may not have any warning signs or symptoms. For this reason, it is essential to measure blood pressure regularly. A new study has shown that consuming foods rich in flavonoids can help patients with high blood pressure. This advantage of these compounds is due to their vasodilator properties. Flavonoids are a diverse group of biologically active polyphenol compounds found in plants and herbs. Regular consumption of flavonoids has cardioprotective effects and may reduce the onset or progression of many cardiovascular diseases, especially hypertension. The article search was done in PubMed, ScienceDirect, and Google Scholar databases. The current body of evidence supports the ingestion of flavonoids for their beneficial effect on blood pressure. However, more significant research should further investigate the vascular moderating effects and the safety and acceptability of almond consumption.